2015
DOI: 10.1371/journal.pone.0144611
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of the Antimicrobial Activity of Different Antimicrobial Peptides against a Range of Pathogenic Bacteria

Abstract: Analysis of a Selected Set of Antimicrobial PeptidesThe rapid emergence of resistance to classical antibiotics has increased the interest in novel antimicrobial compounds. Antimicrobial peptides (AMPs) represent an attractive alternative to classical antibiotics and a number of different studies have reported antimicrobial activity data of various AMPs, but there is only limited comparative data available. The mode of action for many AMPs is largely unknown even though several models have suggested that the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
114
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(127 citation statements)
references
References 64 publications
(64 reference statements)
6
114
0
2
Order By: Relevance
“…AMPs kill a wide range of species, including fungi and viruses (46)(47)(48) as well as Gram-positive and Gram-negative bacteria, including Listeria monocytogenes, Staphylococcus aureus, Salmonella enterica serovar Typhimurium, Escherichia coli, and Pseudomonas aeruginosa (49). However, AMPs, which are ribosomally produced, exhibit unfavorable properties for use as antimicrobial therapies, such as susceptibility to degradation, cytotoxicity to host cells, instability with heat or enzymes, and a high cost of production (50,51). It might be worth noting that most nonribosomal antimicrobial peptides, such as polymyxin, fusaricidin, and daptomycin, are "lipopeptides" which contain a mixture of charged residues and aliphatic tails and act by disrupting cell membrane or cell wall function (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…AMPs kill a wide range of species, including fungi and viruses (46)(47)(48) as well as Gram-positive and Gram-negative bacteria, including Listeria monocytogenes, Staphylococcus aureus, Salmonella enterica serovar Typhimurium, Escherichia coli, and Pseudomonas aeruginosa (49). However, AMPs, which are ribosomally produced, exhibit unfavorable properties for use as antimicrobial therapies, such as susceptibility to degradation, cytotoxicity to host cells, instability with heat or enzymes, and a high cost of production (50,51). It might be worth noting that most nonribosomal antimicrobial peptides, such as polymyxin, fusaricidin, and daptomycin, are "lipopeptides" which contain a mixture of charged residues and aliphatic tails and act by disrupting cell membrane or cell wall function (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…In general, natural or synthetic AMPs interact with negatively charged phospholipids present in the outer membrane of pathogens rather than the host cells, which presents neutral phospholipids (zwitterionic). Therefore, AMPs have been investigated regarding their antileishmanial and antibacterial properties [28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…It was previously shown in vitro that these three AMPs have a bactericidal effect (Ebbensgaard et al . ). However, cytotoxicity studies revealed that CAP11 and CAP11‐1‐18m2 were able to elicit lysis of rainbow trout RBCs after which these AMPs were excluded from the study.…”
Section: Discussionmentioning
confidence: 97%
“…These AMPs showed generally high in vitro antimicrobial activities, that is minimum inhibitory concentration (MIC) value of 2–64 mg L −1 , against Gram‐negative bacteria including Y. ruckeri (Ebbensgaard et al . ).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation